Measuring and analyzing the efficiency of the performance of the municipalities of the Mayoralty of Baghdad using the data envelope analysis methodology (Eurasian Journal of History, Geography and Economics, 2022)
Measuring the efficiency of the performance of the municipalities of the Mayoralty of Baghdad is one of the tools used in determining how to use the resources available to these municipalities, and to achieve the well-being of the population of the municipalities of the research sample, and to achieve sustainable development and some of its indicators. The aim of the research is to assess the efficiency and specific factors in the municipalities of the Mayoralty of Baghdad during the period (2021-2019) using the data envelope analysis (DEA) methodology by panel data. And using the inputs and outputs of these municipalities to determine the efficient and inefficient municipalities. and reference municipalities with full technical proficiency, DEAP 2.1 program has been implemented. The research concluded that there were four municipalities that were not technically efficient in using their resources, which are: Al-Kadhimiya Municipality, AlDora Municipality, Al-Rasheed Municipality, and Al-Sadr Municipality out of a total of (13) municipalities, which indicates that they are working at the lowest level of production. Its relative efficiency is less than (100%). In addition, Al-Sadr Municipality has shown increased returns, enabling it to expand its activity and achieve the optimum efficiency scale. There are also three municipalities that showed Diminishing Returns (AlKadhimiya municipality, Al-Dora municipality, and Al-Rasheed municipality), which means that they did not reach the optimal combination of their resources. It did not reach the optimum level of output, and it is unable to expand its activity and reach optimal efficiency, and despite large allocations for capital and operational expenditures in some municipalities, it did not fulfill its role in satisfying the needs of the population in those municipalities of clean water and getting rid of pollution. environment, and was unable to achieve the requirements of sustainable development. The researchers recommend that inefficient municipalities should resort to the reference municipalities that have achieved 100% efficiency, to see their working methods and planning methods, as well as to increase the inputs of inefficient municipalities in order to address the imbalance in efficient municipalities